2023
DOI: 10.1021/acs.joc.3c00093
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Accessing Trifluoromethyl Carbinol-Containing Chromones from o-Hydroxyaryl Enaminones and Trifluoroacetaldehyde/Ketone Derivatives

Abstract: Herein, we present a practical strategy for the direct construction of structurally diverse trifluoromethyl carbinolcontaining compounds, especially CF 3 -substituted tertiary alcohol with chromone derivatives from easily available o-hydroxyaryl enaminones and trifluoroacetaldehyde/ketone derivatives under metal-free conditions. This reaction features a broad substrate scope with good yields and is easily scaled up. Notably, a one-pot in two-steps reaction of obtained products with amidines is also developed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Because BHX is a neutral bidendate ligand that often coordinates with metal ions through nitrogen atoms, the IR spectra of the newly synthesized complexes were collected in the range 400–4000 cm −1 (Table 2) and helped to identify regions of absorption due to the corresponding vibrations 1,22 . It was found that the BHX ligand's v (NH 2 ) bending and stretching vibrations were shifted in complexes from 3200 and 649 cm −1 to 3235–3332 and 613–689 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because BHX is a neutral bidendate ligand that often coordinates with metal ions through nitrogen atoms, the IR spectra of the newly synthesized complexes were collected in the range 400–4000 cm −1 (Table 2) and helped to identify regions of absorption due to the corresponding vibrations 1,22 . It was found that the BHX ligand's v (NH 2 ) bending and stretching vibrations were shifted in complexes from 3200 and 649 cm −1 to 3235–3332 and 613–689 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Metal complexes can carry out biological reactions on their own including ligand replacement and redox reactions if the active species of medicines contain them. Thus, it is anticipated that identifying the active species in biological interactions will provide useful information regarding the potential therapeutic applications of metal complexes 1 . A mucolytic medication called bromhexine hydrochloride (BHX) is used to treat respiratory illnesses that are accompanied by productive cough and viscous or abundant mucus.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, inspired by these appealing transformations, we recognized an opportunity to realize the selective triple bond cleavage of CF 2 Br 2 to access monofluorinated heterocyclics. Based on our long-term research interest in radical chemistry and fluorinated heterocyclics, we herein report a successful realization of novel radical-polar crossover enabled triple cleavage of CF 2 Br 2 with enamines and aryl sulfonyl hydrazines under photocatalytic conditions, affording a variety of valuable 3-fluoropyrazole derivatives (Scheme c). This approach not only offers a step-economic route to high-value-added polyfunctionalized fluoropyrazole derivatives but also unlocks the novel reactivity of CF 2 Br 2 , which was first used as a C1F1 unit.…”
mentioning
confidence: 96%
“…Our group recently focused on the cross-coupling of simple starting materials to synthesize complex heterocycles . As a continuation of our interest in the construction of heterocycles, we envisioned using fluorination reagents to produce radicals via a photocatalytic process, which further underwent radical addition reactions with α-diazoketones to generate radical intermediate I .…”
mentioning
confidence: 99%